Inhibition of JNK-Mediated Autophagy Promotes Proscillaridin A- Induced Apoptosis via ROS Generation, Intracellular Ca+2 Oscillation and Inhibiting STAT3 Signaling in Breast Cancer Cells - Saleem, Muhammad Zubair; Alshwmi, Mohammed; Zhang, He; Din, Syed Riaz Ud; Nisar, Muhammad Azhar; Khan, Muhammad; Alam, Shahid; Alam, Gulzar; Jin, Lingling; Ma, Tonghui (Frontiers in Pharmacology, 2020)
Breast cancer is the most heterogenous cancer type among women across the world. Despite concerted efforts, breast cancer management is still unsatisfactory. Besides, interplay between apoptosis and autophagy is an imperative factor in categorizing therapeutics for cancer treatment. Proscillaridin A (PSD-A), a well-known cardiac glycoside used for cardiac arrest and arrythmias, has been unveiled in many cancer types but the underlying mechanism for apoptosis and autophagy in breast cancer is not fully understood. In our study, PSD-A restricted cell growth, inhibited STAT3 activation and induced apoptosis and autophagy in breast cancer cells via ROS generation and Ca+2 oscillation. Pretreatment of NAC and BAPTA-AM restored PSD-A induced cellular events in breast cancer cells. PSD-A induced apoptosis via DNA fragmentation, caspase-cascade activation, PARP cleavage, mitochondrial dysfunction, Bax/Bcl-2 proteins modulation and ER chaperone GRP78 inhibition along with decreased phosphorylation of ERK1/2. Inhibition of STAT3 activation was found to be associated with decreased phosphorylation of SRC. Moreover, PSD-A induced events of autophagy i.e. conversion of LC3-I to LC3-II, and Atg3 expression via JNK activation and decreased mTOR and AKT phosphorylation. In this study, pretreatment of SP600125, a JNK inhibitor, reduced autophagy and enhanced STAT3 inhibition and apoptosis. Additionally, SB203580, a commercial p38 inhibitor, stimulated STAT3 activation and improved autophagic events rate in breast cancer cells that displays role of MAPK signaling pathway in interplay between apoptosis and autophagy. Our data suggest that rate of apoptotic cell death is improved by blocking JNK-induced autophagy in PSD-A treated MCF-7 and MDA-MB-231 breast cancer cells.